The pedagogical opportunities of learning English grammar independently - Ergasheva Durdona Faxriddin qizi, Utayeva Iroda Baxodirovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, we view the pedagogical chances of learning english grammar independently, especially the available resources and ways of improving grammar at home without taking courses. Information about the importance of self-study while learning grammar is also given.